Pengaruh Leverage, Likuiditas, dan Pertumbuhan Penjualan terhadap Profitabilitas pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia (Periode 2021 – 2024) - Dian Lestari; Arif Makhsun; Sri Astuti (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research aims to analyze the effect of leverage, liquidity, and sales growth on profitability in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The study used a purposive sampling method with 69 companies and 276 observation data. The data were analyzed using multiple linear regression through SPSS version 26 after classical assumption tests. The results show that leverage (Debt to Equity Ratio) has a negative effect on profitability, while leverage (Debt to Asset Ratio) has no effect. Liquidity measured by the Current Ratio has a positive effect, while the Quick Ratio has no effect on profitability. Sales growth positively affects profitability. Simultaneously, leverage, liquidity, and sales growth significantly influence profitability (Return on Assets) in food and beverage companies. These findings imply that companies should maintain an optimal capital structure and liquidity level to sustain profitability amid competition in the food and beverage sector.